IDENTIFIKASI SENYAWA FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN EKSTRAK KASAR DAUN PEPE - Prayoga, Dewa Gede Eka; Nocianitri, Komang Ayu; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i02.p01, 2019)
This research was conducted to identify the phytochemical compounds and antioxidant activity of pepe leaves (Gymnema reticulatum Br.) crude extract in various solvent types . The experimental design used in this research was a completely randomized design with solvent type treatments consisting of 5 types : aquadest, ethyl acetate 96%, acetone 70%, ethanol 70%, and methanol 95%. The treatment was repeated three times, so that 15 experimental units were obtained. Qualitative data obtained in this research were displayed with tables, while quantitative data were analyzed by variance and if the treatment had a significant effect, then followed by Duncan's test. The results showed that the treatment of solvent types affected phytochemical compounds that was extracted from pepe leaves and had a significant effect (P<0.01) on yield, total phenol, total flavonoids, and antioxidant activity. The best results showed that 70% acetone solvents were able to extract phytochemical compounds from alkaloids, saponins, phenols, flavonoids, and steroids in the form of sterols and had the highest antioxidant activity based on 62.06% free radical inhibition percentage with IC50 values of 200.775 mg/L, yield 32.35%, total phenol 36.14 mgGAE/g extract, and total flavonoids 50.37 mgQE/g extract.